Hepatitis C virus E2 envelope glycoprotein produced in Nicotiana benthamiana triggers humoral response with virus-neutralizing activity in vaccinated mice - Dobrica, M; van Eerde, A; Tucureanu, C; Onu, A; Paruch, L; Caras, I; Vlase, E; Steen, H; Haugslien, S; Alonzi, D; Zitzmann, N; Bock, R; et al. (Wiley, 2021)
Chronic infection with hepatitis C virus (HCV) remains a leading cause of liver-related pathologies and a global health problem, currently affecting more than 71 million people worldwide. The development of a prophylactic vaccine is much needed to complement the effective antiviral treatment available and achieve HCV eradication. Current strategies focus on increasing the immunogenicity of the HCV envelope glycoprotein E2, the major target of virus neutralizing antibodies, by testing various expression systems or manipulating the protein conformation and the N-glycosylation pattern.